PERDEBATAN ULAMA TENTANG KEMURTADAN; ANALISIS PERSPEKTIF FIKIH DAN IMPLIKASI SOSIAL HUKUM DI INDONESIA - Nia Maulina; Billy Mandenas; Syamsul Arbentoni (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2026)
The scholarly debate on apostasy constitutes an important issue in Islamic legal studies, as it relates to the relationship between belief, religious freedom, legal authority, and social order. This article aims to analyze the views of Muslim jurists on apostasy from the perspective of fiqh and to examine its socio-legal implications in the Indonesian context. This study employs a normative juridical method with conceptual and historical approaches, through an examination of classical fiqh literature, contemporary Muslim legal thought, and relevant principles of Islamic law. The findings indicate that the debate on apostasy is not limited to the legal status of apostates, but also includes evidentiary requirements, intentionality, the public dimension of the act, and its relationship to threats against social order. Some classical jurists regarded apostasy as a serious violation with specific legal consequences, whereas a number of contemporary scholars emphasize the need to interpret this issue within the framework of maqāṣid al-sharī‘ah, the protection of human dignity, and the realities of the modern rule-of-law state. In Indonesia, apostasy is not regulated as a distinct criminal offense; however, it has social, administrative, and religious implications. This article affirms the importance of a proportional, contextual, and public-interest-oriented fiqh approach so that debates on apostasy do not generate social conflict, discrimination, or violations of justice in a plural society.